Marine algae of St. Martin's Island, Bangladesh- II. Brown algae - Islam, AKM Nurul; Aziz, Abdul; Parveen, Rehana (Bangladesh Journal of Plant Taxonomy, 2004)
No abstract available. Bangladesh J. Plant Taxon. 11(1): 1-8, 2004 (June)